La Justice Libanaise Au Service Des Entreprises - Habib Kazzi (European Scientific Journal, ESJ, 2017)
Inevitable consequence of the fierce competition between the actors of globalization, domestic judicial systems and legal frameworks become a competitive weapon in the same way as a technical business management or financial tactics. In such circumstances, this paper endeavors to emphasize the degree of competitiveness of the Lebanese judicial system through the analysis of the strategic use of certain instruments, seemingly trivial, of our substantive and procedural rules.